Using Drones to Study Human Beings: Ethical and Regulatory Issues - Resnik, David B.; Elliott, Kevin C. (Science and engineering ethics, 2019)
Researchers have used drones to track wildlife populations, monitor forest fires, map glaciers, and measure air pollution but have only begun to consider how to use these unmanned aerial vehicles to study human beings. The potential use of drones to study public gatherings or other human activities raises novel issues of privacy, confidentiality, and consent, which this article explores in depth. It argues that drone research could fall into several different categories: non-human subjects research (HSR), exempt HSR, or non-exempt HSR. In the case of non-exempt HSR, it will be difficult for institutional review boards to approve studies unless they are designed so that informed consent can be waived. Whether drone research is non-HSR, exempt HSR, or non-exempt HSR, it is important for investigators to consult communities which could be affected by the research.